5-year follow-up of spinal and sacroiliac MRI abnormalities in early axial spondyloarthritis: data from the DESIR cohort. Issue 1 (5th February 2020) - Madari, Queeny; Sepriano, Alexandre; Ramiro, Sofia; Molto, Anna; Claudepierre, Pascal; Wendling, Daniel; Dougados, Maxime; van der Heijde, Desirée; van Gaalen, Floris A
Abstract : Objective: To study changes on MRI of the spine and sacroiliac joint (SIJ) in early axial spondyloarthritis (axSpA) over time. Methods: In the Devenir des Spondyloarthropathies Indifférenciées Récentes cohort, MRI-spine and MRI-SIJ at baseline and 2 and 5 years were scored by central readers for bone marrow oedema (BME), fatty lesions, erosions, sclerosis, ankylosis and spinal bone spurs. The average mean number of lesions was reported or the agreement of ≥2 out of 3 readers for binary outcomes. Net progression was calculated by subtracting the patients that 'improved' from those that 'worsened' divided by the total number of patients. Results: Over 5 years, in 155 patients with axSpA (mean age 33.5 (SD 8.9) years, symptom duration 1.4 (0.8) years, 63% human leucocyte antigen+, 14% modified New York+), BME on MRI-SIJ decreased by a mean Spondyloarthritis Research Consortium of Canada score of 1.4 (SD 6.5) (p=0.009). The largest BME decrease was observed in patients using biological disease-modifying antirheumatic drugs at 5 years. Spinal BME increased by 0.3 (4.6) (p=0.41). Fatty lesions and/or erosions on MRI-SIJ increased by a mean of 1.0 (SD 2.6) (p<0.001). Spinal fatty lesions and/or erosions increased by 0.2 (SD 0.5) (p<0.001). Compared with baseline, at 5 years, 7.3% less patients had BME on MRI-SIJ according to the Assessment of Spondyloarthritis International Society definition, while 6.6% more patients had ≥5 fatty lesions and/or erosions. At 5 years, 0.7% less patients had ≥5 spinal BME lesions and 0.7% less patients had ≥5 spinal fatty lesions. Conclusion: Over 5 years, BME on MRI-SIJ decreased and spinal BME remained similar, but numerically, little progression of structural lesions on MRI of the SIJ and spine was seen.